Construct Validity of the Spanish Version of the CHAMPS Questionnaire for institutionalized patients over 65 years old - José M. Cancela; Carlos Ayán; Miguel A. Sánchez-Lastra; Ángel Casal
Abstract This study investigates the construct validity of the Spanish version of the CHAMPS questionnaire with institutionalized older adults between the ages of 74 and 90. Seven days of accelerometer data were collected from 52 participants (mean age 82.40 ± 8.26 years), followed by the administration of CHAMPS. The Barthel Index and the Chair Stand Test were used to assess functional independence and fitness levels. The four scores yielded by CHAMPS showed a low-to-moderate agreement with the data derived from the accelerometer (r=0.253-0.385) and with the Barthel Index (r=0.313-0.519), but no association was established with fitness levels. Additionally, no significant correlations were observed between CHAMPS and the accelerometer when cognitive impairment was considered. The results imply that the Spanish version of CHAMPS shows construct validity to estimate the amount of physical activity performed by institutionalized older adults without cognitive impairment.